Stillbirth Among Patients With Diabetes in Pregnancy in Ethiopia: Systematic Review and Meta-Analysis - Belay, Demeke Mesfin; Bayih, Wubet Alebachew; Alemu, Abebaw Yeshambel; Ayele, Amare Simegn; Mekonen, Demewoz Kefale; Birhane, Binyam Minuye (Frontiers in Pediatrics, 2021)
Abstract Purpose: Maternal diabetes mellitus and the resulting adverse fetal outcomes including stillbirth in low and middle income countries like Ethiopia is high. Thus, setting specific evidence is pivotal to plan, evaluate and improve national preventive measures and helpful to achieve international sustainable development goal. Therefore, this systematic review and meta-analysis is the first in its kind to estimate the pooled prevalence of stillbirths and its determinants among diabetes mothers in Ethiopia. Methods: PubMed, Science direct, Web of science, SCOPUS, Google Scholar and gray literature found in Addis Ababa and Haramaya University online repositories were accessed. Cross-sectional, case-control and cohort studies reported using English language was involved. I2 statistic, egger’s test and funnel plot were used to check heterogeneity and measure publication bias respectively. Weighted inverse variance random effect model was performed. Results: The pooled prevalence of stillbirths among diabetes mothers was 2.39 [95% Confidence Interval (CI); -0.20, 4.97]. Being house wife [Adjusted Odd Ratio (AOR) = 2.11; 95% CI; 1.08, 3.14], low maternal age AOR = 1.04 [95% CI; 1.01, 1.12] and gestational age less than 37 completed weeks AOR = 9.76 [95% CI; 7.29, 12.24] were increased the risk of stillbirth among diabetes mothers. Conclusions: Based on this review, the national effect size of stillbirth among diabetes mother was 2.39%. Low maternal age, gestational age less than 37 completed weeks and being house wife were significant determinants of stillbirths. Trial registration: PROSPERO 2020: CRD4202016774 Keywords: Ethiopia, Diabetes mellitus, Mothers, stillbirths; Systematic review